Critical success factors in strategic alliances for facilities management in business services - Muhammad Al Farissy; Syahrul Nizam Kamaruzzaman (Penerbit Universiti Kebangsaan Malaysia, 2018)
Facilities Management (FM) is a multidisciplinary science that combines the profession to ensure environmental development function are operating effectively and efficiently. In order to effectively perform the task and processes, Critical Success Factors (CSF) is required by an organization to measure success in identifying CSF enterprises. With associated strategic alliances, companies can ensure the business or project has the proper focus to avoid wasted effort. This research aims to determine the critical success factor in the strategy of alliances in the business services for facilities management. A literature review was conducted in order to identify the critical success factor for strategic alliances specifically in the business sector. Medium such as journals, articles, and case studies related to the topic was explored. Moreover, other mediums such as documents, annual reports, electronic documents, rules and regulation and others that are related to this topic were explored and analysed. The critical success factors from the literature review were extracted and discussed. From this study, there are seven (7) critical success factors were found to be the influential factors in implementing strategic alliance in facilities management. Building relationship alliance in facilities management strategies not only bring the impact of the alliance partner but also bring impact to end users.